Representation of Category of Intertextuality in a Scientific Text - Dalieva Madina Khabibullaevna (Researchparks Publishing, 2021)
The article discusses the issues associated with representation of category of intertextuality in a scientific text. In this work, the actualization of the category of intertextuality is studied from the standpoint of the cognitive-discursive approach, which made it possible to determine both the composition of knowledge transmitted by intertextual inclusions and the functional purpose of these linguistic means in scientific texts. Intertextuality as one of the categories demonstrates itself in a scientific text with the maximum degree of intensity, which is due to the institutional nature of scientific knowledge and the dialogic nature of scientific communication, as well as the main purpose of the scientific text to be a means of storing, representing and transmitting scientific knowledge and opinions, taking into account the history of the development of science.